2018
DOI: 10.3390/ijms19103238
|View full text |Cite
|
Sign up to set email alerts
|

AMPK: An Epigenetic Landscape Modulator

Abstract: Activated by AMP-dependent and -independent mechanisms, AMP-activated protein kinase (AMPK) plays a central role in the regulation of cellular bioenergetics and cellular survival. AMPK regulates a diverse set of signaling networks that converge to epigenetically mediate transcriptional events. Reversible histone and DNA modifications, such as acetylation and methylation, result in structural chromatin alterations that influence transcriptional machinery access to genomic regulatory elements. The orchestration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 79 publications
3
32
0
Order By: Relevance
“…AMPK is known to influence chromatin accessibility e.g., via modulated histone acetylation (e.g., Gongol et al, 2018). Notably, AMPK −/− cells displayed higher global acetylation of selected lysine residues on histone 3 (K14,18, 27, and 56) ( Supplementary Figure 3), possibly causing a dilution effect of Nrf2 by more accessible binding sites in the knockout cells, as previously outlined (Brewster et al, 2014;Rydenfelt et al, 2014).…”
Section: Wt and Ampk−/− Cells Do Not Markedly Differ In The Local Chrsupporting
confidence: 53%
See 1 more Smart Citation
“…AMPK is known to influence chromatin accessibility e.g., via modulated histone acetylation (e.g., Gongol et al, 2018). Notably, AMPK −/− cells displayed higher global acetylation of selected lysine residues on histone 3 (K14,18, 27, and 56) ( Supplementary Figure 3), possibly causing a dilution effect of Nrf2 by more accessible binding sites in the knockout cells, as previously outlined (Brewster et al, 2014;Rydenfelt et al, 2014).…”
Section: Wt and Ampk−/− Cells Do Not Markedly Differ In The Local Chrsupporting
confidence: 53%
“…acetylation (Gongol et al, 2018) and an increased global histone acetylation in the used AMPK −/− cells compared to wt cells. Notably, examined ARE sites appeared to be within relatively loosely packed chromatin throughout all tested conditions.…”
Section: Discussionmentioning
confidence: 94%
“…These genes can also be found to be methylated, with PGC1a modifications affecting mitochondrial density in type 2 diabetic patients [ 51 , 52 ], and NRF1 methylation causing TFAM (mitochondrial transcription factor A) silencing and a reduction in mitochondrial biogenesis [ 53 ]. In fact, methylation of PGC1a can additionally be modulated by nuclear DNMT3 [ 52 ] or DNMT1, the latter of which can be inhibited by AMPK (AMP-activated protein kinase) phosphorylation [ 54 ]. These studies raise the question of whether differential methylation of nuclear genes controlling the expression and activity of DNMT1 may also indirectly lead to changes in mtDNA methylation.…”
Section: Is Mitochondrial Dna Methylated?mentioning
confidence: 99%
“…While it presents an inhibitory role towards DNMT1, it can also have a stimulatory effect on DNMT3s. The latter takes place as AMPK either transactivates let-7 microRNA which leads to an increase in the SAM/SAH ratio, or it activates serine hydroxymethyltransferase 2 (SHMT2) which converts serine to glycine in the mitochondria, facilitating production of SAM [ 54 ] (Fig. 3 ).…”
Section: Effects Of Mitochondria On Nuclear Dna Methylationmentioning
confidence: 99%
“…Once activated, AMPK phosphorylates several downstream targets [6,[8][9][10], thereby inhibiting energy consumption and promoting energy production to ensure cellular survival [7]. Besides its role as a central hub in cellular energy utilization, AMPK is also involved in a number of other important biological functions (for review see Kahn et al, [11]), including the recently described regulation of the epigenetic pathways ( Figure 1) [11,12]. The first hints of AMPK's cardiovascular influence were shown in 1999 by Chen et al who reported direct phosphorylation sites on endothelial NO-Synthase enzyme in endothelial cells and myocytes [13].…”
Section: Introductionmentioning
confidence: 99%